Energetic Particle Signatures Above Saturn's Aurorae. Issue 1 (9th January 2020) - Bader, A.; Badman, S. V.; Ray, L. C.; Paranicas, C. P.; Lorch, C. T. S.; Clark, G.; André, M.; Mitchell, D. G.; Constable, D. A.; Kinrade, J.; Hunt, G. J.; Pryor, W.
Abstract: Near the end of its mission, NASA's Cassini spacecraft performed several low‐altitude passes across Saturn's auroral region. We present ultraviolet auroral imagery and various coincident particle and field measurements of two such passes, providing important information about the structure and dynamics of Saturn's auroral acceleration region. In upward field‐aligned current regions, upward proton beams are observed to reach energies of several tens of keV; the associated precipitating electron populations are found to have mean energies of about 10 keV. With no significant wave activity being apparent, these findings indicate strong parallel potentials responsible for auroral acceleration, about 100 times stronger than at Earth. This is further supported by observations of proton conics in downward field‐aligned current regions above the acceleration region, which feature a lower energy cutoff above ∼ 50 keV—indicating energetic proton populations trapped by strong parallel potentials while being transversely energized until they can overcome the trapping potential, likely through wave‐particle interactions. A spacecraft pass through a downward current region at an altitude near the acceleration region reveals plasma wave features, which may be driving the transverse proton acceleration generating the conics. Overall, the signatures observed resemble those related to the terrestrial and Jovian aurorae, the particle energies and potentials at Saturn appearing to be significantly higher than at Earth and comparable to those at Jupiter. Plain Language Summary: NASA's Cassini spacecraft orbited closer to Saturn than ever before during the last stage of its mission, the "Grand Finale". This allowed the onboard instruments to measure charged particles and plasma waves directly above the auroral region while simultaneously providing high‐resolution imagery of the ultraviolet aurorae. Based on observations of highly energetic ions streaming away from the planet in regions of low plasma wave activity, we infer the existence of strong electric fields which act to accelerate electrons down into the atmosphere, driving the bright auroral emissions. Our estimates of the average energy of the precipitating electrons support this finding. Charged ions sometimes seem to be energized by plasma waves above the aurorae before they can escape, but the exact process in which this happens is not fully understood. Most signatures presented here resemble those observed in relation to Earth's aurorae, suggesting that the mechanisms acting at both planets are quite similar although Saturn's acceleration mechanism is significantly stronger. Key Points: Low‐altitude orbits of Cassini reveal energetic proton and related plasma wave signatures within/above Saturn's auroral acceleration region Observations of proton conics in downward current regions indicate strong parallel electric potentials and transverse heating Observed energies are much higher at Saturn than above the terrestrial aurorae, but the acceleration mechanisms may be of a similar nature